Enhancing Students’ Scientific Argumentation Skills through Nearpod-Assisted Guided Inquiry Learning on the Topic of Heat Transfer - Allya Luqyana Fadia; Umi Windasari; Putri Avianita Salsabila; Anisa Nel Labibah; Farid Nabil Muzaqi; Fikky Dian Roqobih (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2026)
Difficulties in constructing scientific arguments remain a persistent challenge in science learning, particularly in linking evidence with appropriate reasoning. This study aimed to examine the effect of a Nearpod-assisted Guided Inquiry Learning model on students’ scientific argumentation skills based on Toulmin’s Argumentation Pattern (TAP), which includes the components of claim, evidence, and warrant. The research was conducted at MTsN 3 Surabaya with 31 seventh-grade students during the 2025/2026 academic year on the topic of heat and heat transfer. A quasi-experimental one-group pretest–posttest design was employed to investigate changes in students’ scientific argumentation skills before and after the implementation of the learning model. Data were collected through essay-based pretests and posttests and were analyzed according to the scientific argumentation components proposed in TAP. The results indicated a statistically significant improvement in students’ scientific argumentation skills (p < .001) with an average N-gain of 0.65 (medium category). These findings suggest that integrating Nearpod within guided inquiry learning can enhance students’ engagement and support the development of scientific argumentation in science learning contexts.